2015
DOI: 10.1016/j.nonrwa.2014.08.005
|View full text |Cite
|
Sign up to set email alerts
|

On symmetries and conservation laws of the Majda–Biello system

Abstract: In 2003, A.J. Majda and J.A. Biello derived and studied the so-called reduced equations for equatorial baroclinic-barotropic waves, to which we refer as to the Majda-Biello system. The equations in question describe the nonlinear interaction of long-wavelength equatorial Rossby waves and barotropic Rossby waves with a significant midlatitude projection in the presence of suitable horizontally and vertically sheared zonal mean flows.Below we present a Hamiltonian structure for Majda-Biello system and describe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…R S U (η)dη −15.37 (see figure 10 wave turbulence [25]. Interestingly [26] points out our Biello-Majda system has only these four conserved quantities.…”
Section: Comparison To Numerical Simulationsmentioning
confidence: 86%
“…R S U (η)dη −15.37 (see figure 10 wave turbulence [25]. Interestingly [26] points out our Biello-Majda system has only these four conserved quantities.…”
Section: Comparison To Numerical Simulationsmentioning
confidence: 86%
“…We believe that using the technique similar to that of [43] (cf. also [20,44]) it can be shown that in the case of n = −5 equation (13) admits no genuinely generalized symmetries, including those with explicit dependence on T and not just the time-independent ones whose nonexistence follows from the above comparison of (15) with (23), so we are left with just one integrable case of n = −2 which we discuss below.…”
Section: Integrabilitymentioning
confidence: 99%
“…However, unlike the KdV, the system is not completely integrable, even in the relatively simple case α = 1. It was recently shown by Vodová-Jahnová that there are no higher conservation laws [30]. The system scales like the KdV, leading to a critical Sobolev index of − 3 2 .…”
Section: Introductionmentioning
confidence: 98%